Biochar-bacteria-plant combined potential for remediation of oil-contaminated soil - Fang, Xin; Zhang, Mei; Zheng, Pufan; Wang, Haomin; Wang, Kefan; Lv, Juan; Shi, Fuchen (Frontiers in Microbiology, 2024)
Oil pollution is a common type of soil organic pollution that is harmful to the ecosystem. Bioremediation, particularly microbe-assisted phytoremediation of oil-contaminated soil, has become a research hotspot in recent years. In order to explore more appropriate bioremediation strategies for soil oil contamination and the mechanism of remediation, we compared the remediation effects of three plants when applied in combination with a microbial agent and biochar. The combined remediation approach of Tagetes erecta, microbial agent, and biochar exhibited the best plant growth and the highest total petroleum hydrocarbons degradation efficiency (76.60%). In addition, all of the remediation methods provided varying degrees of restoration of carbon and nitrogen contents of soils. High-throughput sequencing found that microbial community diversity and richness were enhanced in most restored soils. Some soil microorganisms associated with oil degradation and plant growth promotion such as Cavicella, C1_B045, Sphingomonas, MND1, Bacillus and Ramlibacter were identified in this study, among which Bacillus was the major component in the microbial agent. Bacillus was positively correlated with all soil remediation indicators tested and was substantially enriched in the rhizosphere of T. erecta. Functional gene prediction of the soil bacterial community based on the KEGG database revealed that pathways of carbohydrate metabolism and amino acid metabolism were up-regulated during remediation of oil-contaminated soils. This study provides a potential method for efficient remediation of oil-contaminated soils and thoroughly examines the biochar-bacteria-plant combined remediation mechanisms of oil-contaminated soil, as well as the combined effects from the perspective of soil bacterial communities.